Surgical Treatment of Cerebral Aneurysms in the Acute Period of Subarachnoid Hemorrhage: Long-Term Result - I. M. Shetova; V. D. Shtadler; P. D. Matveev; V. A. Lukyanchikov; V. V. Krylov (Неотложная медицинская помощь)
The influence of the consequences of aneurysmal subarachnoid hemorrhage on the human body in the long-term period has been insufficiently studied. Most studies indicate a high risk of developing cognitive impairment. Until now, there is no unified algorithm for the management of patients with aneurysmal subarachnoid hemorrhage, who need long-term comprehensive rehabilitation and supervision of specialists in various fields.Aim of study. To study the influence of the nature, severity, features of the clinical manifestation of aneurysmal subarachnoid hemorrhage, as well as the choice of the method of intervention in the acute period of the disease on the long-term results of treatment of aneurysms.Material and methods. In the presented study, the observation group included 74 patients who were operated on in the emergency neurosurgery department of the N.V. Sklifosovsky Research Institute for Emergency Medicine of the Moscow Health Department from 2013 to 2019 in the acute period of subarachnoid hemorrhage (during the first 14 days after the rupture of the cerebral aneurysm). The average age of patients at the time of surgery was 47 [Me=46; min=27; max=76] years old. The ruptured aneurysm was turned off from the bloodstream by one of the following methods: microsurgical intervention with the application of a clip to the aneurysm neck (50 (67,6%) patients), the simultaneous open intervention of aneurysm clipping, and the formation of an extra-intracranial micro anastomosis from the side of the aneurysm access (8 (10,8%) patients), endovascular exclusion of the cerebral aneurysm from the bloodstream (16 (21,6%) patients). On average, after 2,4 [Me=2,5; min=1; max=6] years, patients were invited for a clinical and neurological examination, which included testing according to the Modified Rankin Scale (MRS), the Bartel Index questionnaire, the Mini-Mental Status Scale (MMSS), and the Hospital Anxiety and Depression Scale (HADS). We analysed the changes in the professional activity and habitual lifestyle of patients, as well as the influence of the most common risk factors: arterial hypertension, diabetes mellitus, smoking, on long-term outcomes.Results. In the long-term period of surgical treatment of cerebral aneurysms, on average after 2,4 [Me=2,5; min=1; max=6] years after subarachnoid hemorrhage, 30 (40,5%) patients scored 0 points on the Modified Rankin Scale, 27 (36,5%) patients — 1 point, 6 (8,1%) patients — 2 points, in 6 (8,1%) patients — 3 points, in 4 (5,4%) patients — 4 points and in 1 (1,4%) patient — 5 points. A significant dependence of the degree of disability according to the modified Rankin scale in the long-term period of subarachnoid hemorrhage on the severity of the patient’s condition at discharge from the hospital was revealed according to the Glasgow Outcome Scale (p<0,001). The patient’s age at the time of rupture of the aneurysm independently influenced cognitive functions and the ability to self-care in the long-term period. With an increase in age by 1 year, the score on the short scale of mental status and on the Bartel questionnaire decreased by 0,08 (p=0,03) and by 0,3 (p=0,04), respectively. With the simultaneous presence of intracerebral hemorrhage and the severity of subarachnoid hemorrhage corresponding to grade III according to the Fisher classification, the likelihood of developing anxiety and depressive mental disorders according to the hospital scale of anxiety and depression increased significantly (p><0,01). The development of intracerebral hematoma with aneurysmal hemorrhage contributed to the appearance of hypertension (p><0,05). Conclusion The revealed disorders that persist for several years after the intervention indicate the need for long-term follow-up of patients who underwent intervention for subarachnoid hemorrhage, the development of individual programs for physical and psychological rehabilitation, and clinical examination of persons at high risk. Keywords: subarachnoid hemorrhage, aneurysm, follow-up, low-flow bypass, endovascular intervention>˂ 0,001). The patient’s age at the time of rupture of the aneurysm independently influenced cognitive functions and the ability to self-care in the long-term period. With an increase in age by 1 year, the score on the short scale of mental status and on the Bartel questionnaire decreased by 0,08 (p=0,03) and by 0,3 (p=0,04), respectively. With the simultaneous presence of intracerebral hemorrhage and the severity of subarachnoid hemorrhage corresponding to grade III according to the Fisher classification, the likelihood of developing anxiety and depressive mental disorders according to the hospital scale of anxiety and depression increased significantly (p˂ 0,01). The development of intracerebral hematoma with aneurysmal hemorrhage contributed to the appearance of hypertension (p<0,05). Conclusion The revealed disorders that persist for several years after the intervention indicate the need for long-term follow-up of patients who underwent intervention for subarachnoid hemorrhage, the development of individual programs for physical and psychological rehabilitation, and clinical examination of persons at high risk. Keywords: subarachnoid hemorrhage, aneurysm, follow-up, low-flow bypass, endovascular intervention>˂ 0,01). The development of intracerebral hematoma with aneurysmal hemorrhage contributed to the appearance of hypertension (p˂ 0,05).Conclusion. The revealed disorders that persist for several years after the intervention indicate the need for long-term follow-up of patients who underwent intervention for subarachnoid hemorrhage, the development of individual programs for physical and psychological rehabilitation, and clinical examination of persons at high risk.